MENINGKATKAN KECERDASAN NATURALIS ANAK MELALUI KEGIATAN BERKEBUN (Penelitian Tindakan di TK B Embun Pagi Islamic School Kalimalang Jakarta Timur Tahun 2015) - dwikayani, yozi - (Tumbuh Kembang, 2018)
Purpose of research to increase naturalistic intelligence in early childhood through gardening activities. The research was conducted on a group K2B Kindergarten Embun Pagi Islamic School Kalimalang the number of 12 children, was conducted from September to November 2015. This study used action research methods (Action research) by Kemmis and Taggart. This study consisted of two cycles, each cycle consisting of 8 sessions / actions. Data analysis using quantitative and qualitative data. Quantitative data analysis with descriptive statistics that compare the results obtained from the first cycle and the second cycle. Analysis of qualitative data by analyzing data from the field notes and interviews during the study to the steps of data reduction, data display and data verification. At 48.18% pre-cycle, the first cycle increased to 62.41% and the second cycle into 84.46%. The results showed an increase naturalistic intelligence in early childhood K2B group carried through gardening activities